The Analysis of the Roles of Bitcoin, Ethereum, and Gold as Hedge and Safe-Haven Assets on the Indonesian Stock Market before and during the COVID-19 Pandemic - Wijaya, Carla A.; Ulpah, Maria (The Indonesian Capital Market Review, 2022)
The uncertainty due to the COVID-19 outbreak has encouraged investors to look for value hedging instruments to minimize risk, which can be in the form of hedging assets or safe-haven assets. In response to it, this study aims to find out whether Bitcoin, Ethereum, and gold can behave as hedging and safe-haven assets before and amid the pandemic in Indonesia. The strategy is by observing the effects of volatility and return of Bitcoin, Ethereum, and gold on the Indonesian stock market. This study employed both quantile regression and simple linear regression models on data of daily closing price taken before and during COVID-19. This study finds that they can be hedge and safe-haven assets during the COVID-19 pandemic in Indonesia. The findings show some significant correlations between assets that can help investors determine which assets can be hedging instruments.